Metro TV’s Editorial Strategy to Controversial Sources: The Case Study on Special Report TV Program - Aristia Ningrum, Dian; Briandana, Rizki; Mulyana, Ahmad (Jurnal Komunikasi, 2024)
One strategy to pique viewers' interest is to display contentious topics, cases, and sources. Metro TV successfully achieved this with their Special Report, "Becoming a Suspect, Rafael Alun Talks". This study was conducted to learn more about Metro TV's editorial approach to airing contentious sources on the Rafael Alun episode of the Special Report show. The idea of editorial strategy and the Hierarchy of Influence theory are used as analytical tools in this study. A case study using a qualitative approach is the methodology employed, and post positivism is the paradigm. The study's findings demonstrate that Metro TV's editorial strategy for airing the Rafael Alun edition of the Special Report consists of five key components: (1) picking topics that are popular and relevant to the general public, as well as their sources; (2) choosing the concept for the program; (3) choosing the team that produces the content; (4) processing the content in line with editorial and editorial direction; and (5) evaluation.